Education in Rwanda : Rebalancing Resources to Accelerate Post-Conflict Development and Poverty Reduction - World Bank (Washington, DC, 2013)
Rwanda's recent history was marred by genocide in 1994, in which at least ten percent of the population lost their lives, and, rebuilding the stock of human capital is an important part of that process, where the government has made efforts to broaden access to education, and enhance the quality of services. On the international stage, the education sector has also come into the limelight, specifically under the 2000 United Nations Millennium Declaration, and, the foregoing context presents clear challenges for education managers. The purpose of this report is to provide a factual basis for discussion. Noteworthy, are the efforts to reduce grade repletion in primary education; and, similarly, reforms in higher education finance have been launched to reduce the cost of government-sponsored overseas studies. The report is addressed to Rwanda's policymakers in the education sector, as well as to education practitioners, and, should also be of interest to policymakers in other parts of the government, particularly those charged with managing the country's development strategy, and aligning public spending accordingly. The breadth of its coverage is limited to key economic aspects that are particularly relevant in the Poverty Reduction Strategy Paper (PRSP) context: cost, finance, service delivery, and education outcomes. Most impressive, is the rapid pace of enrollment increase in the aftermath of the genocide, and, as the system expanded, it has done so in ways that has moved it toward a good balance between the public, and private sectors, while also compares favorably with that of other low-income countries in Africa, in terms of the socioeconomic disparities in educational access. Challenges ahead focus on managing student flow, and graduate output, mobilizing, and making effective use of resources for education, ensuring that public resources for education reach the front lines, balancing the accessibility of schools against considerations of scale economies, managing classroom conditions, and processes to enhance student learning, and, minimizing the barriers to education for orphans, and other vulnerable groups. Nevertheless, the task ahead remains daunting as the recovery phase gives way to the implementing the sector's long-term development. Concerns about efficiency, equity, and fiscal sustainability will be inevitably relevant, as the country seeks to advance educational progress in a resource-constrained environment.